NUMERICAL INVESTIGATION OF LAMINAR MIXED CONVECTION IN A SQUARE CROSS-SECTIONED CYLINDRICAL ANNULAR ENCLOSURE - Turan, Osman (Yildiz Technical Univ, 2020)
Steady-state laminar mixed convection of Newtonian fluids in a square cross-sectioned cylindrical annular enclosure with rotating inner wall and heated top cover has been numerically analysed based on axisymmetric incompressible flow simulations. Richardson number, Reynolds number and r(i)/R effects on heat and momentum transport have been investigated for the range of Richardson number 0 <= Ri <= 1, Reynolds number 500 <= Re <= 2000 and 0.25 <= r(i)/R <= 8 at a representative value of Prandtl number (i.e Pr = 1.0). A scaling analysis has been also carried out in order to elucidate the possible influences of Reynolds, Richardson and Prandtl numbers and r(i)/R on the mean Nusselt number. It has been found that the mean Nusselt number (Nu) over bar demonstrates a monotonically decreasing trend with increasing Ri whereas (Nu) over bar increases with increasing r(i)/R and Re which is consistent with scaling estimation. It is also observed that the flow pattern in the case of purely forced convection (i.e Ri > 0) is significantly different from those in mixed convection (i.e Ri > 0). In the case of Ri = 0 (i.e. purely forced convection), a one-cell flow structure with two small vortexes on the top corners is observed for r(i)/ <= 1, whereas a second cell appears in the flow field for r(i)/R > 1 at Re = 1000. On the other hand, in the case of mixed convection (i.e Ri > 0), two-cell and four-cell flow structures occur in the flow field depending on Ri and r(i)/R for the range of Ri, Re and r(i)/R considered here at Pr = 1.0. Based these observations, a flow regime diagram has been proposed here for mixed convection (i.e Ri > 0) for the range of Ri, Re and r(i)/R analysed in this study.
Keywords: Mixed Convection; Rotating Wall; Richardson number; Cylindrical Enclosure; Annular Enclosure